Environmental constraints on the lipid composition and metabolism of euphausiids:the case of Euphausia superba and Meganyctiphanes norvegica - Mayzaud, P; Albessard, E; Virtue, P; Boutoute, M (Canadian Journal of Fisheries and Aquatic Sciences, 2000)
Antarctic (Euphausia superba) and northern krill (Meganyctiphanes norvegica) are characterised by largescalespatial distributions. Euphausia superba is limited to the Southern Ocean, while M. norvegica is present from theArctic Ocean to the Mediterranean Sea. Euphausia superba structural lipids showed little mesoscale variability. Specificdifferences between phosphatidylcholine and phosphatidylethanolamine fatty acid composition exceeded variability relatedto sampling stations. On a larger scale (Southern Ocean), fatty acid composition of both total polar lipids andphosphatidylcholine confirmed the reduced level of regional variability. Similar comparisons between femaleM. norvegica collected at two extreme sites in terms of temperature regime (Kattegat and Ligurian Sea) during twoseasons (springsummer and fallwinter) suggested a more complex picture. Levels of phosphatidylethanolamine,lysophosphatidylcholine, and diphosphatidylglycerol showed significant differences between sites. During springsummer, a lower content of phosphatidylethanolamine and lysophosphatidylcholine was observed for the Ligurian Seapopulation. Fatty acid composition of total polar lipids was significantly different at both sites. Comparisons betweenspringsummer populations at both sites showed higher percentages of 22:6n3 and a lower content in saturated andmonoenoic acids for the Ligurian Sea, suggesting some degree of adaptation to temperature regime. 103